Kerala's Power Predicament: Issues and Solutions - M P Parameswaran (Economic and Political Weekly September 15, 1990, 1990)
Till 1983, when the state became energy deficient, Kerala exported electricity to other states. For two decades from 1962 'abundant hydro-power/export of energy/profit' has been the guiding philosophy of the Kerala State Electricity Board. This deterred the board from thinking about thermal power Today the state depends entirely on the hydro-system for its electricity needs. However, realistic hydro-energy estimates fall far short of the projected electricity demand. An overview of the electrical energy policy pursued by the state and its deficiencies and a programme of action